Research the causes of formation of internal pores (blowholes) in welded joints of metal wire cord - I. V. Borisovets; T. P. Kurenkova; A. A. Sakharnaja (Литьë и металлургия)
Analysis of the research results shows that about 20% of defective weld joints of the metal wire cord are destroyed due to the presence of internal pores in the weld zone. The article analyzes the results of the work carried out in the laboratories of the Belarusian metallurgical works – the management company of the Belarusian metallurgical company holding, and identifies possible causes of this defect in the structure of welded metal wire cord joints.